Pelatihan Bahasa dan Pengenalan Budaya Kerja Jepang bagi Siswa SMK NU Miftahul Huda Kepanjen Malang - efrizal, efrizal; Prihandari, Ismi; Dewi, Fitriana Puspita; Setyanto, Aji (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
Vocational School NU Miftahul Huda Kepanjen is one of the vocational schools in Indonesia that received a government assistance program to prepare non-English overseas internships in 2024. Since 2023, Vocational School NU Miftahul Huda has been holding a Japanese language training program to prepare its graduates to work in Japan following a technical internship program. otherwise known as the Ginou Jisshuusei program. In 2023, approximately 25 graduates of Vocational School NU Miftahul Huda will have taken Japanese language training and in 2024 as many as 23 students will take part in the overseas internship preparation program and 16 of them will receive government assistance. Vocational school graduates have technical skills and have many opportunities to work abroad, especially in Japan, to get decent work and improve family welfare as well as economic growth. This is in line with the SDGs (Sustainable Development Goals) which are global and national commitments in an effort to improve the welfare of society. SDGs is a sustainable development program in which there are 17 goals with 169 measurable targets with specified deadlines. Getting decent work for all and sustainable economic growth is one of the SDGs.